2018
DOI: 10.5897/ajar2015.9941
|View full text |Cite
|
Sign up to set email alerts
|

Wet bulb dimensions associated with different flow and terrain declivity

Abstract: Geometry information of wet bulb is important for the design of projects and management of drip irrigation, mainly to estimate the volume of wet soil, emitter flows and irrigation time. This study aims to determine the dimensions of wet bulb formed by drippers with different flow and terrain declivities. For this, soil moisture levels were determined throughout the soil profile after drip irrigation with three flow emitters associated with four terrain declivities. It was verified that when the terrain was in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…The percentage of a localized irrigation system due to declivity can lead to an increase of up to 8.86% per hectare (Cunha et al, 2014). Souza et al (2018) concluded that the slope influences the dimensions and geometry of the wet bulb.…”
Section: Introductionmentioning
confidence: 99%
“…The percentage of a localized irrigation system due to declivity can lead to an increase of up to 8.86% per hectare (Cunha et al, 2014). Souza et al (2018) concluded that the slope influences the dimensions and geometry of the wet bulb.…”
Section: Introductionmentioning
confidence: 99%
“…Another factor to be considered in evaluating the uniformity of water and fertilizer distribution in drip fertigation systems is the slope of the lateral line. This is because topography has an influence on the uniformity of flow and pressure, as well as on pH, electrical conductivity, among others (Souza et al, 2018). According to (Szekut et al, 2018) the operation of lateral drip lines is affected by the topography of the irrigated area and represents, depending on the type of water applied, changes in the discharge characteristics of emitters.…”
Section: Introductionmentioning
confidence: 99%